The value of student consultancy projects for hospitality businesses. (10th April 2019) - Slater, L.; Lim, W.M.; Lean, J.
The purpose of the study is to explore hospitality businesses perceptions of value related to their participation in student consultancy projects. In-depth semi-structured interviews were conducted with managers of six businesses working with student consultancy teams studying for a degree in tourism and hospitality at a UK HEI. Thematic qualitative analysis was used to identify recurrent themes regarding the perceived value of the consultancy activity to the business. The research finds that perceptions of the value of consultancy projects are influenced by a number of factors including the knowledge obtained through the activity, the amount of time committed and the satisfaction gained through contributing to students' learning. Businesses considering engagement with universities through student consultancy projects can utilise the findings to assist in making a realistic appraisal of the value of such activity. Universities seeking businesses to support student consultancy modules can use the findings to inform discussions with prospective clients. Whilst previous studies have focused on the learning value of student consultancy projects to students, this paper examines their value from the perspective of businesses. The study develops an understanding of value that takes account of the contextually unique characteristics of student consultancy.